1998
DOI: 10.1159/000027307
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoexfoliation Syndrome: A Cohort Study on Intraoperative Complications in Cataract Surgery

Abstract: Our aim was to determine the rate of intraoperative complications induced by pseudoexfoliation syndrome (PSX) in cataract surgery. We report our experience regarding 1,052 consecutive patients who underwent phacoemulsification. Exact logistic regression was used to examine the role of PSX in intraoperative complications. Odds ratio for intraoperative complications (vitreous loss, capsular break, zonular break) was estimated to be 5.1 for PSX present as compared to when it is absent. PSX was associated with a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
2
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 13 publications
5
48
2
5
Order By: Relevance
“…Lumme et al [7] found significantly higher rates of intraoperative complications including zonular rupture, posterior capsule rupture, and vitreous loss (14.8%, 10.2%, and 7.4%, respectively) during cataract surgery on eyes with PEX, and suggested that zonular and posterior capsule rupture are important risk factors for vitreous loss. Scrolli et al [16] also found higher intraoperative incidences of zonular dialysis, posterior capsule rupture and vitreous loss in PEX patients undergoing phacoemulsification than in patients without pseudoexfoliation. Avramides et al (21) found that 61.9% of the patients with PEX had a pupil diameter of less than 5 mm, and the incidence of intraoperative complications in these patients was as follows: zonulolysis, 13.09%; posterior capsule tear, 10.71%; and vitreous loss, 7.14% [21].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Lumme et al [7] found significantly higher rates of intraoperative complications including zonular rupture, posterior capsule rupture, and vitreous loss (14.8%, 10.2%, and 7.4%, respectively) during cataract surgery on eyes with PEX, and suggested that zonular and posterior capsule rupture are important risk factors for vitreous loss. Scrolli et al [16] also found higher intraoperative incidences of zonular dialysis, posterior capsule rupture and vitreous loss in PEX patients undergoing phacoemulsification than in patients without pseudoexfoliation. Avramides et al (21) found that 61.9% of the patients with PEX had a pupil diameter of less than 5 mm, and the incidence of intraoperative complications in these patients was as follows: zonulolysis, 13.09%; posterior capsule tear, 10.71%; and vitreous loss, 7.14% [21].…”
Section: Discussionmentioning
confidence: 91%
“…It is considerably more difficult to achieve sufficient pupillary dilation for cataract surgery in eyes with PEX than normal eyes [8,15,16]. Iris haemorrhage, corneal endothelial damage, lens dislocation, vitreous loss, posterior capsule rupture and sphincter rupture occur more frequently in eyes with insufficient intraoperative pupillary dilation during cataract extraction [15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Since PXS has been linked to multiple pathological entities of the eye including glaucoma, cataract, perioperative complications during eye surgery [19][20][21][22][23][24] and postoperative complications after cataract surgery 25 , it is of utmost importance to recognize ocular manifestations of PXS. Pseudoexfoliation (PEX) at baseline was identifi ed as an independent risk factor for primary open-angle glaucoma (POAG) and relation between increased intraocular pressure (IOP) and PXS was established in diff erent studies 26,27 , suggesting obstruction of the aqueous humor outfl ow.…”
Section: Introductionmentioning
confidence: 99%
“…Patients were dilated with mydriatic-cycloplegic drops and NSAIDS were used to maintain dilatation. Pupillary diameter after dilatation was measured and graded as poor (2-4mm), moderate (5-6mm), and good (7-9mm or more) [7]. Cataract was graded according to LOCS III grading system.…”
Section: Methodsmentioning
confidence: 99%